Effect of food ingredients on glucagon‐like peptide‐1 secretion in STC‐1 and HuTu‐80 cells. (10th June 2019) - Yue, Yuan; Madsen, Sidsel; Hedemann, Mette Skou; Knudsen, Knud Erik Bach; Sparsø, Flemming Vang; Laursen, Anne; Jensen, Henrik Max; Knudsen, Tine Ahrendt; Purup, Stig
Summary: This study aims at identifying food ingredients that have potential to enhance satiety and therefore potentially can be used for preventing and treating obesity. To do so, effects of thirteen food ingredients on the secretion of gut satiety hormone glucagon‐like peptide‐1 (GLP‐1) in enteroendocrine STC‐1 and HuTu‐80 cells were investigated. First, the effects of food ingredients on cell viability were investigated. This was done to determine if the individual ingredient affected cell viability, and in case so, to determine the ingredient concentration below which, the cell viability was unaffected. Enzyme‐treated whey protein, palmitic acid, stearic acid, green tea extract, and hesperidin did not affect GLP‐1 secretion. Functional soy protein, fractionated functional soy protein, acetylated monoglyceride, N‐oleoylethanolamine, epigallocatechin‐3‐gallate, hesperetin, rosemary extract, and kale extract increased GLP‐1 secretion in at least one cell line. However, the effects of the eight potent ingredients on GLP‐1 secretion need to be further investigated in vivo . Abstract : Thirteen food ingredients were tested for their effects on the secretion of gut satiety hormone glucagon‐like peptide‐1in enteroendocrine STC‐1 and HuTu‐80 cells. Viability assays were first performed to ensure the cell viability maintained above 80% during the study. Eight out of 13 ingredients were found to induce GLP‐1 secretion in vitro .